Implement of Digital Moire technique on DSP for alignment of partial compensation interferometer. (January 2016) - Tian, Yuhan; QunHao; YaoHu; Wang, Shaopu; Li, Tengfei; Wang, Jingxian
Abstract: Digital Moiré technique is adopted in partial compensation interferometer (PCI) for high-precision testing of figure error of the aspheric surfaces. The figure error of the measured aspheric is obtained by a series of calculation with the real interferogram and ideal interferograms generated by computer. The dense interference fringes at the exit pupil make it difficult to align the PCI. On the contrary, digital Moire fringes composed from real and ideal interferograms are sparse and corresponding to the figure error of the measured aspheric, making it easier to align the PCI. Generally, digital Moire technique is processed on the computer, resulting in slow processing speed and difficult display in real time. Digital Signal Processor (DSP) can be used to implement digital Moire technique and display digital Moire fringes in real time with its powerful processing capacity. In this paper, digital Moire technique is implemented on the TMS320C6455 DSP. The hardware system consists of a DSP module, a CCD camera and a monitor. Finally we experimentally obtain the digital Moire image, and further analyze how to align the PCI theoretically.